Brine shrimp lethality assay - Quazi Sahely Sarah; Fatema Chowdhury Anny; Mir Misbahuddin (Bangladesh Pharmacological Society, 2017)
Brine shrimp lethality assay is an important tool for the preliminary cytotoxicity assay of plant extract and others based on the ability to kill a laboratory cultured larvae (nauplii). The nauplii were exposed to different concentrations of plant extract for 24 hours. The number of motile nauplii was calculated for the effectiveness of the extract. It is a simple, cost effective and requires small amount of test material. Video Clip of Methodology: Brine Shrimp Lethality Assay: 4 min 9 sec   Full Screen   Alternate